Perception of Pseudo-Stereoscopic Image Depths of Three-Dimensional Objects Displayed on VDT Screen - Muraoka, T.; Ikeda, H. (2007 5th IEEE International Conference on Industrial Informatics, 2007)
The subjective evaluation was carried out to check if we can feel the pseudo-stereoscopic image depth of a three-dimensional object taken from a video camera and displayed on the VDT screen. Whether an image of the three-dimensional object displayed on the VDT screen was recognized planar or three-dimensional by the subjects was found to depend on the incident angle of light onto the three-dimensional object when the video camera located at 45 degrees from the horizontal ground line on the VDT screen to the position of eyes of each subject, perpendicular to the ground line, measured from the object. An experimental study of the perception of the pseudo-stereoscopic image depth in a three-dimensional object irradiated by the illuminant located at an angle in the range of 22 to 70 degrees measured vertically from the horizontal line on the VDT screen showed that we could correctly recognize the pseudo-stereoscopic image depth of the three-dimensional object displayed on the VDT screen. Another experimental study carried out under the same conditions except that the illuminant was located at another angle in the range of 46 to 49 degrees measured vertically from the same horizontal line showed that we could strongly recognize the pseudo-stereoscopic image depth. These experimental studies were carried out by 40 subjects with ages of 20 to 26 years old, with differences of visual acuity, between the left and right eyes, of 0.3 or less. The results of these experimental studies verified that the three-dimensional objects displayed on the VDT screen could be perceived quasi-stereoscopic if the objects were irradiated by the illuminant located at suitable positions.